Bypassing bacterial infection in phage display by sequencing DNA released from phage particles. Issue 11 (29th November 2017) - Villequey, Camille; Kong, Xu-Dong; Heinis, Christian
Abstract: Phage display relies on a bacterial infection step in which the phage particles are replicated to perform multiple affinity selection rounds and to enable the identification of isolated clones by DNA sequencing. While this process is efficient for wild-type phage, the bacterial infection rate of phage with mutant or chemically modified coat proteins can be low. For example, a phage mutant with a disulfide-free p3 coat protein, used for the selection of bicyclic peptides, has a more than 100-fold reduced infection rate compared to the wild-type. A potential strategy for bypassing the bacterial infection step is to directly sequence DNA extracted from phage particles after a single round of phage panning using high-throughput sequencing. In this work, we have quantified the fraction of phage clones that can be identified by directly sequencing DNA from phage particles. The results show that the DNA of essentially all of the phage particles can be 'decoded', and that the sequence coverage for mutants equals that of amplified DNA extracted from cells infected with wild-type phage. This procedure is particularly attractive for selections with phage that have a compromised infection capacity, and it may allow phage display to be performed with particles that are not infective at all.